Endourologic management of severely encrusted ureteral stents - Lojanapiwat B. (2014)
Background: Ureteral stents are in common use in urologic practice. Even though the stent is a valuable urological tool, its use has two widely encountered complications, namely, stent encrustation and stone formation. These complications are difficult to manage; but endourologic surgery, which is minimally invasive, has become the first choice in the treatment for encrustation and stone formation. Material and Method: Eight patients with severely encrusted ureteral stents were treated by endourologic techniques. One patient had severe encrustation at all sites of the stent and was treated by percutaneuos nephrolithotomy, ureteroscopy with intracorporeal lithotripsy and cystolitholapaxy. Five patients with severe encrustation at both ends of the stent were treated with percutaneous nephrolithotomy and cystolitholapaxy(4 cases) and with extracorporeal shock wave lithotripsy (ESWL) and cystolitholapaxy. The last two patients with severely encrusted ureteral stents at the bladder end were treated with percutaneous cystolithotomy with intracorporeal lithotripsy and by optical lithotrite, respectively. Results: All cases were stone free and stent free in one session without complication. The average approaches were 1.9 (range 1-3). All stents were removed intact and no subsequent stent was required following the removal of the problematic stent. Conclusion: Endourologic surgery which is minimally invasive surgery, is the first choice of treatment for the management of severely encrusted ureteral stents with good results in one session without complications and no subsequent stent is necessary. The authors recommend removing the stent as soon as possible or change the new stent every 3 months for decreasing the incidence of these complications.